Farewell Luncheon at Cedar Lanes Bowling Alley for Tomar Mason II - Watkins, Howard::::::::: (1986)
Polly Getz, Justice Pauline Davis Hanson, Tomar Mason II and Darlene Azevedo Tomar's legal name is Tomar Mason II; her mother is Tomar Mason